Грамматические и статистические особенности английских абсолютных конструкций - Попович, Е. С.; Попович, Олена Сергіївна; Popovich, Е. S.; Петрова, Е. И.; Петрова, Олена Іванівна; Petrova, Е. І.; Томенко, М. Г.; Томенко, Марина Геннадіївна; Tomenko, М. G. (Одеса, 2017)
У статті розглядається одне з найбільш дискусійних питань теоретичноі граматики англійськоі мови - абсолютні конструкціі. Сформований текстовий корпус у 2,5 млн слововживань дозволив експериментально визначити не тільки різноманіття абсолютних конструкцій у досліджуваних текстах, але й їхні граматичні та статистичні характеристики.

Оne of the most debatable problems of the English theoretical Grammar - absolute constructions - are considered in the paper. The text corpus of 2,5 mil word units gives the opportunity to experimentally indicate not only the variety of absolute constructions functioning in the analyzed texts but also their grammatical and statistical characteristics.
Попович, Е. С. Грамматические и статистические особенности английских абсолютных конструкций / Е. С. Попович, Е. И. Петрова, М. Г. Томенко // Одеський лінгвістичний вісник. – 2017. – Вип. 10. – Т.1. – С. 95-98.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; абсолютний номінатив; проблематична конструкція; структура предикаціі; трансформація; мовна одиниця; absolute nominative; language unit; predication structure; problematic construction; transformation